New Studies for Dynamic Programming and Fractional Differential Equations in Partial Modular b-Metric Spaces - Abdurrahman Büyükkaya; Dilek Kesik; Ülkü Yeşil; Mahpeyker Öztürk (Fractal and Fractional)
This study explores innovative insights into the realms of dynamic programming and fractional differential equations, situated explicitly within the framework of partial modular b-metric spaces enriched with a binary relation <semantics>R</semantics>, proposing a novel definition for a generalized <semantics>ℷC</semantics>-type Suzuki <semantics>R</semantics>-contraction specific to these spaces. By doing so, we pave the way for a range of relation-theoretical common fixed-point theorems, highlighting the versatility of our approach. To illustrate the practical relevance of our findings, we present a compelling example. Ultimately, this work aims to enrich the existing academic discourse and stimulate further research and practical applications within the field.